Exploring Madurese Cultural Symbols in the Film Sangkolan Kona: A Semiotic Analysis Based on Roland Barthes - Dewabrata, Bondan; Wira Fabri, R. Radtya; Eko Rahardjo, Rosnindar Prio; Syakina, Annisa; Habibah, Faridatul (Indonesian Journal Publisher, 2025)
This research explores how cultural and moral values are represented in the local Madurese film Sangkolan Kona using a semiotic analysis approach. The growing role of regional films in shaping cultural identity and promoting local wisdom becomes a critical context for this study. The objective is to uncover the embedded signs and symbols that convey cultural norms, ethical values, and social messages within the narrative and visual elements of the film. This qualitative research employs Roland Barthes’ semiotic theory, focusing on denotation, connotation, and myth to decode the layers of meaning presented in selected scenes and dialogues. Data were collected through documentation and textual analysis of the film, followed by interpretative categorization. The findings reveal that Sangkolan Kona contains strong representations of Madurese values such as familial loyalty, communal solidarity, respect for elders, and moral accountability, expressed through culturally specific signs like traditional attire, local rituals, and idiomatic expressions. These elements not only construct a distinctive cultural identity but also promote ethical reflection among audiences. The study concludes that regional films like Sangkolan Kona serve as effective communicative tools in preserving cultural heritage and transmitting moral values across generations.